Elevated Fasting C-Peptide Levels Correlate with Increased 10-Year Risk of Atherosclerotic Cardiovascular Disease in Newly Diagnosed Type 2 Diabetes Patients - Zha XY; Wei CS; Dong JJ; Wu JZ; Xie LX; Xu ZH; Zheng HQ; Huang DB; Lai PB (Diabetes, Metabolic Syndrome and Obesity)
Xiao-Yun Zha, Chang-Shun Wei, Jia-Jia Dong, Jin-Zhi Wu, Liang-Xiao Xie, Ze-Hong Xu, Hua-Qiang Zheng, Duo-Bin Huang, Peng-Bin Lai The First Department of Endocrinology and Metabolism, Zhangzhou Affiliated Hospital of Fujian Medical University, Zhangzhou, Fujian, 363000, People’s Republic of ChinaCorrespondence: Peng-Bin Lai, The First Department of Endocrinology and Metabolism, Zhangzhou Affiliated Hospital of Fujian Medical University, Zhangzhou, Fujian, 363000, People’s Republic of China, Tel +8613709398727, Email 13709398727@163.comPurpose: This study aims to analyze the impact of serum C-peptide levels in patients with newly diagnosed type 2 diabetes (T2DM) on the 10-year risk of atherosclerotic cardiovascular disease (ASCVD).Patients and Methods: A total of 1923 patients with newly diagnosed T2DM were selected and categorized into four groups based on the interquartile range of fasting C-peptide (FCP) levels: Q1 group (FCP≤ 0.568 ng/mL), Q2 group (0.568 < FCP≤ 0.751 ng/mL), Q3 group (0.751 < FCP≤ 0.980 ng/mL), and Q4 group (FCP > 0.980 ng/mL). Clinical data were collected, and the China-PAR model was employed to evaluate the risk score of ASCVD within 10 years. Additionally, the correlation between FCP levels and the risk of ASCVD was analyzed.Results: As the quartiles of FCP increased, the 10-year ASCVD risk exhibited a gradual increase. The risk score in the FCP > 0.980 ng/mL group was significantly higher than that in the other groups, with noted differences related to gender and weight. Multiple linear regression analysis indicated that, even after adjusting for confounding factors such as gender, age, body mass index (BMI), and glycosylated hemoglobin, FCP levels remained a positive predictor of the 10-year ASCVD risk.Conclusion: High FCP levels are identified as a risk factor for ASCVD within 10 years in patients with newly diagnosed T2DM.Keywords: type 2 diabetes, fasting C-peptide, ASCVD risk